Philanthropy in The Creative Economy Sector: Challenges and Opportunities - Efendi, Mohamad Nur; Khomairoh, Selvina (Al-madinah: Journal of Islamic Civilization, 2024)
This study examines the role of philanthropy in the creative economy sector, focusing on the challenges and opportunities faced through a literature review. The creative economy plays a vital role in economic growth and cultural development, while philanthropy provides critical resources to support creative initiatives. However, the integration of philanthropy in this sector faces several challenges, including alignment between philanthropic goals and the needs of the creative industry, equitable distribution of funds, and evaluation of the impact of philanthropic contributions. The literature suggests that philanthropy can enhance innovation and cultural diversity, but there is a gap in understanding and communication between philanthropists and creative professionals. The effectiveness of philanthropic efforts is often hampered by bureaucracy and a lack of strategic alignment. Opportunities to enhance the role of philanthropy include strengthening collaboration between philanthropic organizations and creative actors, leveraging technology for more efficient fund distribution, and developing metrics to measure the impact of philanthropic investments. This study suggests that a more strategic, inclusive, and transparent approach to philanthropy in the creative economy sector could unlock substantial benefits, promoting innovation, cultural enrichment, and economic resilience. This study provides important insights for developing best practices in philanthropic engagement in the creative economy sector, ensuring that the needs of diverse creative communities are met and sustained.